2020
DOI: 10.1371/journal.pcbi.1008405
|View full text |Cite
|
Sign up to set email alerts
|

Cancer classification based on chromatin accessibility profiles with deep adversarial learning model

Abstract: Given the complexity and diversity of the cancer genomics profiles, it is challenging to identify distinct clusters from different cancer types. Numerous analyses have been conducted for this propose. Still, the methods they used always do not directly support the high-dimensional omics data across the whole genome (Such as ATAC-seq profiles). In this study, based on the deep adversarial learning, we present an end-to-end approach ClusterATAC to leverage high-dimensional features and explore the classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…There are recent demonstrations for the successful applications of deep learning methods for biomedicine, genetics, and genomics (Ainscough et al ., 2018; Eraslan et al ., 2019; Zou et al ., 2019; Arbab et al ., 2020; Kim et al ., 2021), as well as some examples from plant biology and agricultural science (Washburn et al ., 2019; Wang et al ., 2020; Dunker et al ., 2021; Warman et al ., 2021). Owing to the availability of big datasets generated by epigenetic and epigenomic research, it makes sense that deep learning models have shown promise for the identification of DNA methylation (Angermueller et al ., 2017; Holder et al ., 2017; Lv et al ., 2020; Li et al ., 2021), histone modifications (Xu et al ., 2017; Hoffman et al ., 2019), RNA methylation (Sun et al ., 2019; Wang & Wang, 2020), and chromatin interactions (Zhang et al ., 2018a; Yang et al ., 2020). However, these deep learning models are mostly implemented in nonplant species, so whether these models can be applied usefully in plant species remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…There are recent demonstrations for the successful applications of deep learning methods for biomedicine, genetics, and genomics (Ainscough et al ., 2018; Eraslan et al ., 2019; Zou et al ., 2019; Arbab et al ., 2020; Kim et al ., 2021), as well as some examples from plant biology and agricultural science (Washburn et al ., 2019; Wang et al ., 2020; Dunker et al ., 2021; Warman et al ., 2021). Owing to the availability of big datasets generated by epigenetic and epigenomic research, it makes sense that deep learning models have shown promise for the identification of DNA methylation (Angermueller et al ., 2017; Holder et al ., 2017; Lv et al ., 2020; Li et al ., 2021), histone modifications (Xu et al ., 2017; Hoffman et al ., 2019), RNA methylation (Sun et al ., 2019; Wang & Wang, 2020), and chromatin interactions (Zhang et al ., 2018a; Yang et al ., 2020). However, these deep learning models are mostly implemented in nonplant species, so whether these models can be applied usefully in plant species remains unclear.…”
Section: Introductionmentioning
confidence: 99%